Longitudinal Neuropsychological Profile in a Patient with Triple A Syndrome. (9th April 2013) - Mazzone, Luigi; Postorino, Valentina; De Peppo, Lavinia; Vassena, Lia; Fatta, Laura; Armando, Marco; Scirè, Giuseppe; Cappa, Marco; Vicari, Stefano
Abstract : Triple A syndrome is an autosomal recessive disorder characterized by the triad of adrenocorticotropic hormone resistant adrenal insufficiency, achalasia, and alacrima. Our aim was to describe the neuropsychological characteristics and the cooccurring psychopathological and neurological disorders in an Italian male child suffering from Triple A syndrome at the time of admission (T0) and after one year of follow-up (T1). Many difficulties were observed in the motor domain, as well as in manual dexterity and static/dynamic balance domains of the motor task over time. In sharp contrast with previous literature reports on frequent mild cognitive dysfunction in patients with Triple A syndrome, our child did not show any mental retardation. By contrast, he showed an average IQ at T0 with a slight improvement at T1. To our knowledge, this report is the first describing neuropsychological profile and co-occurring psychopathological problems in a child with Triple A syndrome. Considering that the Triple A syndrome is a progressive disorder which can take years to develop the full-blown clinical picture, these patients require periodical medical controls. Moreover, assessment of neuropsychological and psychopathological features should be performed in patients with this disease, in order to underline the variability of this syndrome.